Current Insight into LDLR and PCSK9 Genetic Variants: Investigating Genetic Keys to Cholesterol in a Cohort of Stroke Patients from Yogyakarta, Indonesia - Priskila, Loury; Atmadi, Lenggana Relung; Bagaskara, Arya Taksya; Anggitama, Andreas Mercyan (UI Scholars Hub, 2025)
Background: Stroke is the second leading cause of mortality worldwide. In Yogyakarta, Indonesia, the incidence of stroke (14%) is higher than the national average. We therefore investigated the roles of LDLR rs688 (C/T) and PCSK9 rs562565 (A/G) polymorphisms in familial hypercholesterolemia as predictors of first-time ischemic stroke. Methods: In this case-control study, 119 first-time ischemic stroke patients were divided into dyslipidemia (N = 71) and non-dyslipidemia groups (N = 48). The DNA of the nucleotide polymorphisms LDLR rs688 (C/T) and PCSK9 rs562556 (A/G) was extracted and analyzed using the PCR-RFLP method, and statistical analyses were performed to evaluate their predictive potential. Results: The LDLR rs688 (C/T) CT genotype was the most common in both groups. The TT genotype appeared slightly more frequently in the dyslipidemia group, but no significant association was found with dyslipidemia (p = 0.460). While lipid levels had no significant relationship with LDLR rs688 (C/T), hemoglobin levels differed significantly across the genotypes (p = 0.002), which suggested the biological relevance of hemoglobin. Conclusions: The LDLR rs688 (C/T) polymorphism was not significantly associated with dyslipidemia among the stroke patients. Nonetheless, genotype-related trends related to lipid and hemoglobin levels indicated potential mechanisms that warrant further investigation.